2010
DOI: 10.1152/ajpcell.00036.2010
|View full text |Cite
|
Sign up to set email alerts
|

Somatic ATP release from guinea pig sympathetic neurons does not require calcium-induced calcium release from internal stores

Abstract: Merriam LA, Locknar SA, Girard BM, Parsons RL. Somatic ATP release from guinea pig sympathetic neurons does not require calcium-induced calcium release from internal stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Detectable levels of transcript were obtained for TRPC 1, 3, 4, and 5, but not TRPC 6. Recently, we found that transcripts for TRPC 1, 3, 4, 5, and 6 were present in extracts of the guinea pig sympathetic stellate ganglia (Merriam et al 2010). In addition, Beaudet et al (2000) found previously that transcripts for TRPC 1, 3, and 6 were present in extracts from neonatal cultured rat SCG neurons and rat adult SCG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detectable levels of transcript were obtained for TRPC 1, 3, 4, and 5, but not TRPC 6. Recently, we found that transcripts for TRPC 1, 3, 4, 5, and 6 were present in extracts of the guinea pig sympathetic stellate ganglia (Merriam et al 2010). In addition, Beaudet et al (2000) found previously that transcripts for TRPC 1, 3, and 6 were present in extracts from neonatal cultured rat SCG neurons and rat adult SCG.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used to determine the presence of TRPC transcripts were those used previously to test for TRPC transcripts in extracts of guinea pig stellate ganglia (Merriam et al 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Tissue sections (20 μm stellate, 40 μm right atria and guinea pig midbrain) were processed by direct mounting techniques as described previously [23,24] . In a separate set of experiments stellate neurons were dissociated and maintained in culture media for 3 days as described in detail previously [25–27] prior to a 1 hour exposure to fixative (2% paraformaldehyde containing 0.2% picric acid). The fixed tissue sections or dissociated cells were rinsed in PBS, permeabilized with 0.5% Triton X-100, and incubated at 4 °C overnight with a primary antiserum directed against tyrosine hydroxylase (TH) (mouse monoclonal 1:400 from RBI, Natick MA) and a primary antiserum against galanin (rabbit polyclonal 1:1000 from Phoenix Pharmaceuticals, Burlingame CA).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with group N, the hemodynamic parameters of group S decreased at some time points, and significant difference was presented. The overall trend indicated the perioperative hemodynamic parameters of group S tended to be more stable than that of group N. The mechanism may be associated with the following reactions: SGB can, to some extent, suppress the conduction of cardiopulmonary sympathetic nerves, surgically stimulate the nerve conduction and lower the sympathetic tension to decrease the sympathetic excitability (Merriam et al, 2010), while the general anesthesia suppresses the relative excitation of vagus nerves so that the haemodynamic parameters can remain stable.…”
Section: Discussionmentioning
confidence: 96%